Single-nucleus transcriptomic profiling of the diaphragm during mechanical ventilation - Lei Li; Feng Jiang; Wenyan Hao; Yu Wang; Yaqian Li; Dong Zhang (Scientific Reports)
Abstract Mechanical ventilation contributes to diaphragm atrophy and muscle weakness, which is referred to as ventilator-induced diaphragmatic dysfunction (VIDD). The pathogenesis of VIDD has not been fully understood until recently. The aim of this study was to investigate the effects of 24 h of mechanical ventilation on fibro-adipogenic progenitor (FAP) proliferation, endothelial-mesenchymal transition (EndMT), and immune cell infiltration driving diaphragm fibrosis in a rabbit model. The rabbits were anaesthetized and randomly divided into two groups (n = 3 each group): a control group and an experimental group. Diaphragm nuclei for sequencing were prepared by dissociating and filtering muscle tissue. 10X Genomics Platform for single-nucleus RNA sequencing (snRNA-seq) was used to profile the cells. Normalization and clustering were performed by Seurat, and clusters were manually annotated as different cell types. In this study, we performed differentially expressed genes (DEGs) analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis, pseudotime analysis and high dimensional weighted gene coexpression network analysis (hdWGCNA) to identify the key genes and signaling pathways related to the pathogenesis of VIDD. We further performed quantitative real-time polymerase chain reaction (qRT-PCR) and Western blotting to verify the results of snRNA-seq. The snRNA-seq results showed that acute postmechanical ventilation diaphragm cell changes included an increase in the proportion of fibroblasts and a decrease in the proportion of myofibres. The DEGs, KEGG, hdWGCNA and pseudotime analyses demonstrated that fibro-adipogenic progenitor (FAP) proliferation, endothelial-mesenchymal transition (EndMT) and immune cell infiltration are the three main processes involved in early stage of fibrosis development, among which Pdgfd, Sema3a, Cxcr2, are the corresponding regulatory genes. Glycolysis and the gene Pfkfb3 are also important metabolic factors for fibrosis formation. Negr1 and Mef2c are involved in phrenic nerve ending loss and diaphragm fibre atrophy. The qRT-PCR data showed that the mRNA levels of the genes Pdgfd, Cxcr2, Pfkfb3 and Negr1 were significantly greater in the experimental group than in the control group (P < 0.01), and the expression levels of Sema3a and Mef2c were significantly lower (P < 0.01). Despite limitations, including the lack of functional evaluations to confirm ventilator-induced diaphragm dysfunction (VIDD) and the absence of data validating diaphragm unloading during ventilation, our findings suggest that FAP proliferation and immune cell infiltration may play a role in the early stage of driving diaphragm fibrosis during mechanical ventilation. However, future studies are needed to confirm these findings and investigate the potential mechanisms underlying them.